ANALISIS KUALITAS PENGUNGKAPAN LAPORAN KEBERLANJUTAN SERTA STATUS INDEKS SRI-KEHATI PADA WIKA DAN JSMR - Afifatunnisa Nafia (Jurnal Akuntansi dan Bisnis, 2025)
This study aims to analyze the quality of sustainability report disclosure of PT Wijaya Karya (WIKA) and PT Jasa Marga (JSMR) based on the provisions of POOJK Number 51/2017, and evaluate its implications for participation in the SRI-KEHATI index during the period 2020–2024. This study uses a qualitative descriptive approach with a content analysis method on the sustainability reports of both companies. The results show that the quality of WIKA's sustainability disclosure has increased significantly, reaching the fully applied level since 2022, while JSMR has met all indicators since 2021. However, WIKA was removed from the SRI-KEHATI index in mid-2024, while JSMR remains listed. This finding indicates that the quality of sustainability disclosure is not the only reason for participation in the SRI-KEHATI index. This study recommends increasing transparency and expanding the scope of research.